Implementation of Value Chain Management in Strengthening Distribution Channels: A Business Coaching Study at the Lavida Depot Jakarta - Arfianie Ayu; Dony Abdul Chalid (Eduvest - Journal of Universal Studies, 2026)
The bottled drinking water (air minum dalam kemasan, AMDK) industry in Indonesia faces increasingly intense competition due to the rapid growth in the number of producers and registered brands. This situation prompts PT Harazaki Surya Abadi, the producer of Lavida bottled water, to strengthen its competitiveness by improving its distribution channels. This study aims to analyze and implement value chain management in strengthening distribution channels: a business coaching study at the Lavida Depot Jakarta in the development of the Lavida Jakarta Depot as a strategy to expand distribution coverage and enhance sales performance. The research adopts a business coaching approach, with data collected through interviews, direct observation, and document analysis. The analytical framework includes the Business Model Canvas, Porter’s Five Forces, SWOT analysis, and VRIO framework to identify key problems and strategic needs. The findings indicate that limited distribution reach is the main barrier to Lavida’s market growth. The implementation of value chain management is realized through the design of business processes, development of standard operating procedures, marketing and sales planning, and strengthening of procurement and logistics systems. The results demonstrate that a value chain–based approach improves the operational readiness of the depot in supporting effective and efficient distribution channel strengthening.